Bayesian Estimation for Two Parameters of Weibull Distribution under Generalized Weighted Loss Function - Kadhim, Abtisam J.; Rasheed, Huda A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, Bayes estimators for the shape and scale parameters of Weibull distribution have been obtained using the generalized weighted loss function, based on Exponential priors. Lindley’s approximation has been used effectively in Bayesian estimation. Based on theMonte Carlo simulation method, those estimators are compared depending on the mean squared errors (MSE’s).